Bibliotherapy as a Non-pharmaceutical Intervention to Enhance Mental Health in Response to the COVID-19 Pandemic: A Mixed-Methods Systematic Review and Bioethical Meta-Analysis - Monroy-Fraustro, Daniela; Maldonado-Castellanos, Isaac; Aboites-Molina, Mónica; Rodríguez, Susana; Sueiras, Perla; Altamirano-Bustamante, Nelly F.; de Hoyos-Bermea, Adalberto; Altamirano-Bustamante, Myriam M. (Frontiers in Public Health, 2021)
Background: One of the non-pharmaceutical treatments offered by psychological support is bibliotherapy, which can be described as the process of reading, reflecting and discussing literature to further a cognitive shift. The COVID-19 pandemic demands a response to prevent a peak in the prevalence of mental health problems and to avoid the collapse of mental health services, which are scarce and inaccessible due to the pandemic itself. Methods: A systematic review was carried out to examine relevant studies that asses the effectiveness of bibliotherapy in different clinical settings as a treatment capable of enhancing a sense of purpose and its surrounding values. To achieve this, a four staged systematic review, including a value analysis, was performed. A variant of the model PICO was used for the search strategy, the systematic review was carried out in three databases: PubMed, Bireme and OVID. Starting with 707 studies, after three rounds of different quality criteria, 13 articles were selected for a meta-analysis including a hermeneutical and phenomenological analysis. Results: Our findings showed that there are no research road maps serving as guides to carry out research in the use of bibliotherapy to enhance mental health. Additionally, values such as autonomy and justice were closely linked with positive results in bibliotherapy, through bibliotherapy patients developed several capacities, including the resignification of their own activities through a new outlook of their moral horizon. This implies that bibliotherapy has the potential to have a positive impact in different settings. Conclusions: Our contribution is to offer a road map which presents the state of the art in bibliotherapy research and which will help institutions and healthcare professionals plan clinical and specific interventions with positive outcomes.